2020
DOI: 10.1002/anie.202014072
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐Descriptors for the Performance Prediction of Electro‐Organic Synthesis

Abstract: Electrochemical organic synthesis has attracted increasing attentions as a sustainable and versatile synthetic platform. Quantitative assessment of the electro‐organic reactions, including reaction thermodynamics, electro‐kinetics, and coupled chemical processes, can lead to effective analytical tool to guide their future design. Herein, we demonstrate that electrochemical parameters such as onset potential, Tafel slope, and effective voltage can be utilized as electro‐descriptors for the evaluation of reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…[40] They demonstrated that the electro-descriptors could be used to identify a hot zone leading to good reaction outcomes and they were able to separate reactive and nonreactive species. [55] It should be noted that except for the case of TEMPO-mediated oxidative dehydrogenation of N-heterocycles, for preparative scale electrolysis a constant potential was used. In the economically more interesting form, electrolysis at constant current, the potential is raised to the desired current flow.…”
Section: Nonlinear Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[40] They demonstrated that the electro-descriptors could be used to identify a hot zone leading to good reaction outcomes and they were able to separate reactive and nonreactive species. [55] It should be noted that except for the case of TEMPO-mediated oxidative dehydrogenation of N-heterocycles, for preparative scale electrolysis a constant potential was used. In the economically more interesting form, electrolysis at constant current, the potential is raised to the desired current flow.…”
Section: Nonlinear Methodsmentioning
confidence: 99%
“…After initial development Examples for the application of machine learning in electrochemistry. [55,57,58] and tuning on experimental data from literature on two palladium-catalyzed cross-coupling reactions, they collected results from 1728 HTE experiments covering the complete search space previously defined. Again, a palladium-catalyzed cross-coupling reaction was used for this part of their studies.…”
Section: Automation and Autonomous Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ding and coworkers described an electro-descriptor-diagram to identify regions of high reactivity using overpotential, Tafel slope, and effective voltage ( Fig. 3B ) [ 34 ]. The last term was defined as the voltage required for a given substrate to produce the same current as the model substrate used for optimization.…”
Section: Data-drive Approaches For Electrochemical Reaction Optimizationmentioning
confidence: 99%
“…With the electrochemical conversion of biomass derivatives as a potential means of green chemical production [1][2][3] , electro-organic synthesis is experiencing a revival [4][5][6][7][8][9][10] Compared to conventional catalytic (de)-hydrogenation reactions, electrocatalytic conversion schemes offer several advantages: a) they operate at ambient conditions, b) they can be powered by sustainable electricity from wind and solar energy, and c) they require only water as the proton source instead of expensive hydrogen feeds [11][12][13] . Kolbe electrolysis is a central reaction in electro-organic synthesis since it could be applied to produce longchained hydrocarbons [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%